Synthesis of Ultrahigh Molecular Weight Polyethylene Using MgO/MgCl2/TiCl4 Core–Shell Catalysts. Issue 10 (15th April 2018) - Bando, Yusuke; Chammingkwan, Patchanee; Terano, Minoru; Taniike, Toshiaki
Abstract: In this study, MgO/MgCl2 /TiCl4 core–shell catalysts are employed for the production of ultrahigh molecular weight polyethylene (UHMWPE) particles, motivated by their advantages including simple preparation, ease of morphology control, and a dramatically reduced Cl content. It is found that the MgO/MgCl2 /TiCl4 core–shell catalysts can provide UHMWPE at a reasonable activity, but the agglomeration of the catalyst particles leads to poor morphology of the UHMWPE. The dispersion problem is largely alleviated by modifying MgO nanoparticles with methyl oleate (MO). Thus, the MO‐modified MgO/MgCl2 /TiCl4 core–shell catalyst successfully affords UHMWPE particles of 100–200 µm at a high yield of 8670 g‐PE g‐Cat −1 . Abstract : A MgO/MgCl2 /TiCl4 Ziegler–Natta core–shell catalyst is employed for the production of ultrahigh molecular weight polyethylene (UHMWPE). This catalyst system features facile control of the particle size, simple preparation, and a significantly lower Cl content. By improving the particle dispersion with surface modification, the catalyst successfully affords UHMWPE particles at a high yield.